Design of AQM controllers for IP routers based on H∞ optimal control. (2nd August 2006) - Chen, Qiang; Yang, Oliver W.W.
Based on the recently developed feedback control model for the Transport Control Protocol (TCP), this paper has formulated controller design procedures for Active Queue Management (AQM) in Internet Protocol (IP) routers using the H∞ optimal control theory. The H∞ loop-shaping technique is applied to solve the S/U Mixed Sensitivity Problem (MSP) and S/T/U MSP in the controller design. Different weight functions and their impacts on the system performance are evaluated and discussed. The effectiveness of the designed controller is verified through OPNET simulations.